2017
DOI: 10.15253/2175-6783.2017000200010
|View full text |Cite
|
Sign up to set email alerts
|

Initial care for burned patients in academic nursing education

Abstract: Objective: to describe the experience of Nursing students in the initial care for burned patients. Methods: a cross-sectional study was carried out with 107 Nursing students from four Higher Education Institutions. A modular structured questionnaire divided in three blocks was used. Data were analyzed through descriptive statistics in the Epi Info® 6.04 software. Results: the majority (94.4%) of students reported that initial care for burned patients was addressed in undergraduate courses, but 81.6% considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…O prognóstico é bom, as mortes são muito raras. Crianças e pré-escolares, assim como idosos, devem ser sempre observados por pelo menos seis horas (MESCHIAL, et al, 2013).…”
Section: Resultsunclassified
“…O prognóstico é bom, as mortes são muito raras. Crianças e pré-escolares, assim como idosos, devem ser sempre observados por pelo menos seis horas (MESCHIAL, et al, 2013).…”
Section: Resultsunclassified
“…Essa realidade também foi evidenciada em pesquisa realizada com 107 estudantes do último ano do curso de enfermagem, em que 77 não tiveram a oportunidade de realizar atendimento primário a um usuário queimado, durante a graduação. Além disso, 84 entrevistados consideraram que o conteúdo teórico visto foi superficialmente e insuficientemente para garantir segurança no atendimento 12 . Na área médica, estudo que teve como objetivo avaliar o conhecimento de estudantes de medicina sobre o atendimento inicial ao usuário queimado revelou que houve predomínio nos conhecimentos com relação à classificação das queimaduras, tipo de fluído a ser utilizado na hidratação, cálculo de diurese ideal e uso de protetores gástricos.…”
Section: Discussionunclassified
“…The choice of these scenarios was justified by previous studies carried out in this region that indicated gaps in the academic training and care practices of nurses on AMB. 9 The selection of the subjects took place based on their intention to participate in the research, respecting the number of places available for educational intervention. As inclusion criteria, the following were considered: having completed the online registration form; acting, for a period longer than one year, as an interventionist nurse at the PHC or as an assisting nurse at the ED or being regularly enrolled in the multi-professional internship training in urgency and emergency.…”
Section: /15mentioning
confidence: 99%